A Review of Students Self-Efficacy for Work-Based Learning (WBL) in Technical and Vocational Education and Training (TVET) Programmes - Mohd Yusoff, Nur Zulaikha; Puteh, Saifullizam; Buhari, Rosnawati; Rosyadi, Sa'adilah (Journal of TVET and Technology Review, 2024)
This systematic literature review discussed work-based learning (WBL) in Technical and Vocational Education and Training (TVET) programs. WBL is an educational strategy that integrates real-world work experiences with traditional classroom learning. These programmes aim to bridge the gap between academic learning at the institutions and the demands of the workplace in industry, helping students develop a deeper understanding of their chosen field and enhance their employability, which is directly applicable to their future careers. The focus of this study was on the self-efficacy of students in the WBL programme, which is a component of TVET education in Malaysia. This systematic literature review analysed 10 articles from Scopus, Google Scholar, and ScienceDirect. These findings demonstrate the importance of improving and further developing the WBL program to ensure that graduates from the TVET field have high marketability and employability. These findings reveal that there is a need for further research on students’ self-efficacy for WBL programmes in Malaysia.